1993
DOI: 10.2337/diab.42.2.336
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ponalrestat, an Aldose Reductase Inhibitor, on Neutrophil Killing of Escherichia Coli and Autonomic Function in Patients With Diabetes Mellitus

Abstract: In diabetic subjects, polyol pathway activity might inhibit neutrophil function and cause nerve damage. The effects of ponalrestat, an aldose reductase inhibitor, were assessed on neutrophil intracellular killing of Escherichia coli and on autonomic function in diabetic subjects in a randomized double-blind, placebo-controlled, crossover trial. We studied 31 diabetic subjects with autonomic dysfunction and 21 age- and sex-matched control subjects. During two 12-wk treatment periods, the diabetic subjects took … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…On the other hand, because of the more advanced and potentially less readily reversible stage of autonomic dysfunction in the group given ALA, the probability of improvement could also be higher in the placebo group. There is evidence in favor of the latter view, since prevention of abnormalities in HRV by near-normoglycemia (3,7,31) or drug treatment (14) seems to be more effective than secondary intervention in CAN (8,9,11,12).…”
Section: Conclusion-mentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, because of the more advanced and potentially less readily reversible stage of autonomic dysfunction in the group given ALA, the probability of improvement could also be higher in the placebo group. There is evidence in favor of the latter view, since prevention of abnormalities in HRV by near-normoglycemia (3,7,31) or drug treatment (14) seems to be more effective than secondary intervention in CAN (8,9,11,12).…”
Section: Conclusion-mentioning
confidence: 90%
“…Potential forms of treatment, derived from the current concepts on the pathogenesis of diabetic neuropathy (10) that have been studied in autonomic neuropathy, include the reduction of increased flux through the polyol pathway by aldose reductase inhibitors (11)(12)(13)(14), inhibition of the formation of advanced glycation end products by aminoguanidine (15), and elimination of endoneurial hypoperfusion by vasodilators (16). However, the efficacy of these approaches has not yet been unequivocally established.…”
mentioning
confidence: 99%
“…Some studies showed functional PMN cell abnormalities such as the impairment of chemotaxis [20,21], adherence [22], and ingestion [20,23], which were associated with chronic hyperglycemia [20,23,24]. The respiratory burst of stimulated PMN cells was significantly reduced in both type 1 [23,25] and type 2 diabetic patients [26] with poor metabolic control. It is unclear how the acute changes in short-lasting high glucose and insulin serum levels could impact the potential for infection in a clinical setting.…”
Section: Introductionmentioning
confidence: 97%
“…[166] However, glomerular filtration rate was on average reduced from 140 to 129 mllmin/m 2 after ponalrestat treatment [167] and from 156 to 124 mUminlm 2 after tolrestat treatment [168] for 6 months. Uncontrolled sorbinil treatment improved diabetic periarticular stiffness,[ln,173] but this was not confirmed in a small short term placebo-controlled trial with ponalrestatJl74] ARI treatment for less than 6 months also ameliorated haematological abnormalities, such as increased erythrocyte sorbitol levels, [140,[175][176][177][178] impaired neutrophil killing [ 179] and enhanced platelet aggregation (maintained during 2 years of follow-up); [180] fibrinolysis remained abnormalJ 181] The functional relevance of these haematological improvements is unclear. [168] Other clinical conditions that have improved during ARI treatment for up to 6 months include diabetic keratopathy, during masked [169,170] or unblinded [171] application of ARI eye drops.…”
Section: Short Term Ari Trialsmentioning
confidence: 99%